Genetic and in silico functional characterization of a novel structural variant in the PAH gene by long-reads sequencing and structural modeling - Gallardo, Viviana; Gaete, Alexis; Maldonado, Jonathan; Morales, Paulina; Peña, Angela; Hamilton, Valerie; Faundes, Víctor; Santa María, Lorena (Frontiers in Genetics, 2025)
IntroductionPhenylketonuria (PKU) is an inherited metabolic disorder caused by biallelic variants in the PAH gene, leading to phenylalanine accumulation and progressive neuronal damage. Over 3,000 variants have been described worldwide; however, a previously unreported exon duplication was identified in Chile, whose genetic and functional characteristics remained unknown.MethodsA patient carrying a duplication of exon 2 in the PAH gene, previously detected by MLPA, was analyzed using nanopore sequencing coupled with CRISPR/Cas9 enrichment (nCATS) to determine the location, size, and orientation of the variant. Specific fragment amplification by PCR and Sanger sequencing was subsequently performed on samples from this patient and seven additional individuals to confirm the presence of the structural variant. Structural modelling of the resulting PAH protein was also conducted to predict functional consequences.ResultsThe nCATS technique identified a ∼18 kb tandem duplication between exons 1 and 3 of the PAH gene. This exon duplication was confirmed by PCR and Sanger sequencing in all eight patients. Additionally, an adenine insertion was detected at the junction site of the duplication. Structural modelling predicted an additional N-terminal segment that would likely interfere with sensing of phenylalanine.DiscussionThe clinical, genetic and in silico functional characterization of this variant, using nCATS and structural modeling, suggests a mild, but relevant alteration in PAH enzymatic function. These findings support the delineation of genotype-phenotype correlations for complex structural variants, which may contribute to the development of personalized therapeutic strategies, while enriching both national and international PKU variant databases.